If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 = x + -6 Reorder the terms: 1 = -6 + x Solving 1 = -6 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 1 + -1x = -6 + x + -1x Combine like terms: x + -1x = 0 1 + -1x = -6 + 0 1 + -1x = -6 Add '-1' to each side of the equation. 1 + -1 + -1x = -6 + -1 Combine like terms: 1 + -1 = 0 0 + -1x = -6 + -1 -1x = -6 + -1 Combine like terms: -6 + -1 = -7 -1x = -7 Divide each side by '-1'. x = 7 Simplifying x = 7
| 3(2x-1)+2=5x-1 | | x+4y+2z=0 | | 2x-3y+2=2 | | 6+4a=-8 | | 0.66r=8 | | 72=-3(x+4)-21x | | K-7=10 | | 3+z=18 | | 1.5r=8 | | -5x=18-3x | | 0.8m=80 | | -6+4y=-12 | | 5x-4(x-6)=1 | | h=-16t^2+150t+1 | | 2x+y=10-3x | | 2x^2-15x+15=8-x^2-5x | | (u+3)2=2u+11u+15 | | X^4-7x+3=0 | | 2x^4-7x+3=0 | | 2x+3x-15=25 | | -2+x-4x=11 | | 5(6)+3(7)= | | -4+3x=-12+25xfraction | | 2y-4*0=10 | | x-2 = 9 (4-10x)4 | | 9y-5y-9=48.80 | | W-8=23 | | 2y+-4*-2=10 | | -42=-6(z-3) | | 5x+9=82-8x | | -3k^2g-[4kg^2-(6k^2g-2kg^2)]=0 | | 3x-3y+3=2 |